An Approach for Constructing Evaluation Model of Suitability Assessment of Agile Methods using Analytic Hierarchy Process - Mikulėnas, G.; Butleris, R. (Elektronika ir Elektrotechnika, 2010)
Agile methods are rapidly growing in popularity software development methods that are not suitable everywhere due to their specifics. The results of previous researches including agility criteria and weights construction are used in this research. The approach for the construction of evaluation models of the suitability assessment of agile methods at IT companies is presented. The terms and concepts used for the approach are defined. The process of the construction the evaluation model is presented. A widely used Analytic Hierarchy Process (AHP) method is used for the construction of the relative weights of agility criteria. The case study of the creation concrete evaluation model is presented. The example of the usage of the constructed evaluation model at some IT company is presented. The accuracy check of the correctness of evaluations is performed. The conclusions of the research are presented, stating that proposed approach increases the effectiveness of the use of agile methods and facilitates the process of suitability evaluation.